Overview of Personality Assessment Instruments - Structural Personality Test and Mahover - Randjelović, Kristina; Todić, Tijana (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
There are differences among psychologists in defining the term personality. The argumentative system of assumptions about personality components and their mutual interaction and/or development is called theory of personality. In personality psychology, we can talk about personality models, which mostly relate to the structure of personality, and quality models must meet the conditions that qualitative theories fulfill. Some of the contemporary models are lexical, biosocial and circular. Katel pointed out that psychological science requires measurement precision, validity of explaining behavior, and reliability of predictions. A number of techniques are used for measuring and researching personality. Inventories are an instrument that measures several constructs. Personality tests can be objective and projective, with the help of which bypass, indirectly diagnose in-depth personality traits. Тhe aim of this paper was to present two instruments (objective and projective) for personality assessment, designed (Structural Personality Test) and adapted (Machover Technique) by Professor Kostić. The motives for the construction and adaptation of the instruments will be discussed, as well as their structure and description of the instruments. This article also presents a comparison of the adapted Machover techniqueby Professor Kostic with the original version by author Karen Machover. Also, it will be discuss the possibilities of applying the instruments for practical and scientific research purposes, outlining their advantages and disadvantages.